THE EFFECTS OF CORN FLOUR WITH TEMPEH FLOUR SUPPLEMENTATION FEEDING IN DIABETES MELLITUS WISTAR RATS TOWARD BLOOD GLUCOSE LEVEL - Asmarani, Fatifa; Wirjatmadi, Bambang; Adriani, Merryana (Universitas Wijaya Kusuma Surabaya, 2015)
Background: Diabetes mellitus (DM) is metabolic disorder syndrome characterized by hyperglycemia due to deficiency of insulin secretion. Patients of diabetic patients increases each year, so it needs proper handling. Corn flour is a source of carbohydrates with a low glycemic index to help reduce the rise in blood sugar levels. In addition, supplementation with tempeh flour containing isoflavones act to protect cells from free radical thereby inhibiting damage cells. Fiber in tempeh affect blood glucose levels because it slows the absorption of glucose.Objective: To determine the effect supplementation of corn flour with tempeh flour on blood sugar levels in diabetes mellitus Wistar rats.Methods: The study was true experimental design with Pre-posttest control group design, samples were 20 male Wistar rats aged 2-3 months were then divided into 4 groups (T0, T1, T2, T3.) T0 was injected with alloxan as 30 mg / 150 grams of BB rats are subsequently treated with standard diet; T1 was dministered by standard diet 50% + 50% corn flour; T2 was administered by standard diet 50% + 30% + corn flour tempeh flour 20%; and T3 was administered by standard diet of corn flour 50% + 15% + 35% tempeh flour for 2 weeks. Blood glucose levels were measured with a glucose kit (GOD FS). Research data were analyzed by One Way ANOVA followed by Tukeys Post Hoc test p-value <0.05.Results: There were significant differences on blood sugar levels in all groups (p = 0.000): control group (only dietary standards), T1 (administered by standard diet 50% + corn flour 50%), T2 (administered by a standard diet 50% + cornstarch 30% tempeh flour + 20%) and T3 (administered by standard diet of corn flour 50% + 15% + 35% tempeh flour).Conclusion: corn flour with tempeh flour supplementation effect on decresing of blood sugar levels.